Pengaruh E-Wom, Variety Seeking, Dan Kualitas Produk Terhadap Brand Swiching Mahasiswi Universitas Islam Malang Yang Berpindah Merek Ke Wardah - Guci, Aji Rokhmad; Rachma, N.; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), Variety Seeking, and Product Quality on Brand Switching behavior among female students of Universitas Islam Malang who switched to Wardah cosmetic products. This research employs a quantitative explanatory research method. Data collection was carried out through questionnaires distributed to 80 female students of Universitas Islam Malang who use Wardah products. The sampling technique used is purposive sampling. Data analysis shows that E-WOM, Variety Seeking, and Product Quality simultaneously contribute 79% to Brand Switching, while the remaining 21% is influenced by other variables not included in this research model.The research results indicate that E-WOM, Variety Seeking, and Product Quality significantly influence Brand Switching among Wardah cosmetic users. Individually, each variable also significantly affects consumers' decisions to switch to Wardah products. These conclusions provide important insights for Wardah's marketing strategy in retaining and attracting new consumers. Keywords : Electronic Word of Mouth, Variety Seeking, Product Quality, Brand Switching, Wardah, Universitas Islam Malang.